Is there a risk for bacterial transmission from surgical marker pens?. Issue 2 (October 2020) - Brinskelle, P.; Koenig, E.; Sendlhofer, G.; Baumhackl, K.A.; Winter, R.; Sawetz, I.; Kamolz, L.P.; Steinmetz, I.; Friedl, H.; Lumenta, D.B.
Summary: Markers for preoperative skin marking are used several times and bear a risk of transmitting bacteria. Bacterial contamination was assessed by sonication and culture. Antimicrobial susceptibility testing (AST) was performed for facultative pathogens to assess multi-drug resistance (MDR). An accelerated failure time model was applied to assess the statistical relationship between the bacterial contamination and the filling status of markers. Of 45 markers, 13 had a colony count <10 cfu/mL and 32 had counts from 10 to 12, 500 cfu/mL. Three markers were colonized by Staphylococcus aureus . No MDR bacteria were found. We recommend single use of markers to reduce transmission risk.